Advanced intelligent computing theories and applications : with aspects of artifical intelligence : Third International Conference on Intelligent Computing, ICIC 2007, Qingdao, China, August 21-24, 2007 : proceedings - International Conference on Intelligent Computing (3rd : 2007 : Qingdao, China); Huang, De-Shuang; Heutte, Laurent; Loog, Marco (Berlin : Springer, 2007)
39